lmmunomodulatory Effects of Human Milk upon Immune Functions in Infants - Ariyanto Harsono; Anang Endaryanto; Muhammad Faizi (Indonesian Pediatric Society, 1999)
Human milk is capable to modulate the immune system in infants in several ways. lmmunorestoration is mostly dominated by immunoglobulins content of human milks especially secretory lgA, although lgG antibody also plays important role. Nucleotide content of human milk is among substances widely investigated all over the world, capable to potentiate immune response in infants by increasing NK cell activity and production of lL-2. lmmunopotentiation also the result of cell content activity of human milk, interferon, and complement. Special feature of anti-inflammatory propertyÂ of human milk is its capability to prevent of allergic disease in infants. This because ofprotein in breast milk is species specific, instead the role of secretotry lgA inÂ preventing absorption of foreign macromolecules. Other substances also play an important role in the antiinflammatory properties of human milk and interestingly the paucity of initiators and mediators in human milk.